Early Childhood Care and Education – A Perspective - Yadav, Padma (THE PRIMARY TEACHER, 2006)
Universally, the early childhood years are expected to lay the foundation for inculcation ofbasic values and social skills in children. It is believed that these values are imbibed from the family as sanskaras and the scriptures advocate an attitude of lalayat or indulgence as the desirable mode of child rearing at this stage. Consequently, in the past, much of the early care and education of the child was informal, within the family and largely through grandmother’s caring practices, stories, and traditional infant games, handed down from one generation to the next. This wealth of developmentally appropriate childcare practices is gradually becoming extinct in view of more modern provisions for children and changing social realities.